Margaret Atwood's The Penelopiad : giving Penelope a voice - Paiva Henriques, Sara (2017)
This study approaches the way in which a narrative told from a feminine point of view, and mainly focused on the domesticity of life, can subvert Odysseus’ story in Margaret Atwood's The Penelopiad. Furthermore, the focus on power relations – one of Atwood’s recurring themes – takes a detour from what would or could be its archetypal representation; thus, in The Penelopiad, both victim and victimizer roles are constantly put at stake, subverted. In this book, Penelope’s passivity facing the death of her twelve maids burdens her with guilt, about which she gives an afterlife account while dwelling in Hades.